The Effect of foreign direct investment on structural change in developing countries: an examination of the labor productivity dimension - Ezo Emako; Seid Nuru; Mesfin Menza (Cogent Business & Management, 2022)
Developing countries require overall labor productivity to sustain their economic growth. Overall labor productivity, on the other hand, cannot be achieved without structural change. Because developing countries lack sufficient resources, foreign direct investment (FDI) is recommended for them to realize structural change. Therefore, the primary purpose of this study is to estimate the effect of FDI on the structural change in labor productivity in developing countries from 1990 to 2018 using Driscoll and Kraay's estimation. The study found that foreign direct investment boosts overall labor productivity by facilitating "structural change" and improving "within-sector" labor productivity. Furthermore, variables such as export, population size, domestic capital, human capital, and the usage of chemical fertilizer all have a positive and significant effect on labor productivity. On the contrary, government expenditure, the development of infrastructure, and the utilization of large areas of land have all been discovered to have a negative effect on labor productivity. However, per capita income has a negligible effect on it. Therefore, developing countries should not only pay attention to the quantity of FDI but also to its quality by putting an emphasis on FDI in the manufacturing sector and export-based FDI. Additionally, increasing domestic capital through the mobilization of domestic savings and strengthening the use of technology, such as chemical fertilizer, may be essential policy directions to increase labor productivity.
Keywords: 650; Driscoll and Kraay; foreign direct investment; labor productivity; structural change; within sector